2023
DOI: 10.3390/molecules28166035
|View full text |Cite
|
Sign up to set email alerts
|

Zanubrutinib Ameliorates Cardiac Fibrosis and Inflammation Induced by Chronic Sympathetic Activation

Abstract: (1) Background: Heart failure (HF) is the final stage of multiple cardiac diseases, which have now become a severe public health problem worldwide. β-Adrenergic receptor (β-AR) overactivation is a major pathological factor associated with multiple cardiac diseases and mediates cardiac fibrosis and inflammation. Previous research has demonstrated that Bruton’s tyrosine kinase (BTK) mediated cardiac fibrosis by TGF-β related signal pathways, indicating that BTK was a potential drug target for cardiac fibrosis. Z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…We have compiled the previous research on anti-organ brosis drugs in our research group, as well as summarized the pharmacological and pathogenic mechanisms. Considering the alleviating effect of zanubrutinib on cardiac brosis [11] , its protective effect on acute lung injury [9] , and the alleviating effect of bortezomib-induced lung injury in mice [10] , we ultimately discovered that zanubrutinib can effectively alleviate the progression of experimental IIM-ILD. To the best of our knowledge, this is the rst evaluation of the dual inhibitory effect of a BTK inhibitor on both IIM and ILD in an IIM-related ILD animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have compiled the previous research on anti-organ brosis drugs in our research group, as well as summarized the pharmacological and pathogenic mechanisms. Considering the alleviating effect of zanubrutinib on cardiac brosis [11] , its protective effect on acute lung injury [9] , and the alleviating effect of bortezomib-induced lung injury in mice [10] , we ultimately discovered that zanubrutinib can effectively alleviate the progression of experimental IIM-ILD. To the best of our knowledge, this is the rst evaluation of the dual inhibitory effect of a BTK inhibitor on both IIM and ILD in an IIM-related ILD animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Zanubrutinib is a second-generation BTK inhibitor that exhibits stronger BTK target occupancy and lower off-target effects compared to the rst-generation BTK inhibitor, ibrutinib. Current research has found that Zanubrutinib has good e cacy in LPS-induced acute lung injury [9] , bleomycin-induced pulmonary brosis in mice [10] , and sympathetic stress-induced cardiac brosis [11] .…”
Section: Introductionmentioning
confidence: 99%